2017
DOI: 10.1007/s11064-017-2225-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Impairs Neurogenesis and Induces Glial Reactivity in the Hippocampus

Abstract: The incorporation of newborn neurons with increased synaptic remodeling and activity-dependent plasticity in the dentate gyrus enhances hippocampal-dependent learning performances. Astrocytes and microglial cells are components of the neurogenic niche and regulate neurogenesis under normal and neurophatological conditions leading to functional consequences for learning and memory. Although cognitive impairments were reported in patients after spinal cord injury (SCI), only few studies have considered remote ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…Moreover, flow cytometry analysis demonstrated that moderate/severe SCI in C57BL/6 male mice caused significantly increased levels of proinflammatory cytokine IL6 in the brain ( Figure 2 ). These data complemented microscopy findings showing chronic microglial activation in brain after SCI [ 38 , 39 , 40 , 73 , 74 ]. Glial activation was confirmed in the sub-granular zone and molecular layer of the DG in the hippocampus in a severity-dependent manner; such activation was only found in moderate and severe SCI, but not mild [ 73 ].…”
Section: Neuroinflammation and Neurodegeneration In The Brain Aftesupporting
confidence: 87%
“…Moreover, flow cytometry analysis demonstrated that moderate/severe SCI in C57BL/6 male mice caused significantly increased levels of proinflammatory cytokine IL6 in the brain ( Figure 2 ). These data complemented microscopy findings showing chronic microglial activation in brain after SCI [ 38 , 39 , 40 , 73 , 74 ]. Glial activation was confirmed in the sub-granular zone and molecular layer of the DG in the hippocampus in a severity-dependent manner; such activation was only found in moderate and severe SCI, but not mild [ 73 ].…”
Section: Neuroinflammation and Neurodegeneration In The Brain Aftesupporting
confidence: 87%
“…More specifically, our findings revealed that there is no significant change in proliferation, evidenced by BrdU uptake, between leopard geckos within intact (original) tails and those induced to self-detach their tails. In contrast, among mammals the hippocampal formation is particularly sensitive to spinal cord injuries 36 , 69 . For example, in rats a partial hemisection of the cervical spinal cord results in a significant reduction in the number of BrdU+ cells within 7-days following injury 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Such effects may underlie a well-known increase in frequency of the brain-affecting neurodegenerative diseases after SCI. Indeed, widespread neuroinflammation and microglia activation are landmarks of neurodegeneration in the brain ( 16 ), and several studies have already shown that SCI promotes these processes, also disturbing neurogenesis ( 17 19 ). Nevertheless, molecular mechanisms of delayed alterations outside the area of injury have been poorly explored.…”
Section: Introductionmentioning
confidence: 99%